Penyalahgunaan Akun Instagram Perihal Penipuan Jual Beli Secara Online Ditinjau dari UU ITE dan Pasal 378 KUHP tentang Penipuan - Putri Prameswari Sudin; Roria Magdalena; Enni Soerjati Priowirjanto; Deasy Soeikromo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to find out about the misuse of social media to commit criminal acts of fraud. The problem is focused on how to avoid online buying and selling scams. Data were collected through secondary data sources. This scientific article aims to determine the regulation of forms of fraud in online transactions, especially on Instagram media. This research uses primary, secondary and tertiary legal materials research methods. The analytical technique used is to use deductive thinking patterns, namely a way of thinking on basic principles. This study concludes that Based on the foregoing description, the conclusion is that legal arrangements regarding criminal acts of fraud are generally regulated in Article 378 of the Criminal Code, namely regarding acts of benefiting oneself or others by violating the law by using a false name or false dignity by deceit or by using false names. a series of lies that move other people to hand over something to him or to give debts or write off receivables is different from online fraud which is specifically regulated in article 28 paragraph (1) of Law Number 11 of 2008 concerning Electronic Information and Transactions as amended into Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), namely the act of intentionally and without rights spreading false and misleading news that results in consumer losses in Electronic Transactions onic.